Increasing Professional Commitment through Strengthening Transformational Leadership and Personal Value With Job Satisfaction as Intervening Variable - Wardani, Andri Kusuma; Hidayat, Nandang; Patras, Yuyun Elizabeth (Pandawan, 2023)
Education is one of the bases first for realizing ambition development economy and prosperity for whole citizens. In terms of this education is one determinant quality source of energy people and the position of education in the process of development is very important. Learning could increase on-site skills and productivity work share results best, and influence the development process economy of a country. Study this carried out at the Bogor State University PGRI. Study this use study quantitative. In research, this, step of methodological data analysis begins with an analysis of statistics descriptive, an analysis of location research, and an analysis path. Leadership is transformational (X1) for involvement professional (Y), coefficient path (y1) = 0.304, 2) Private value (X2) for involvement professional (Y), coefficient path (y2) = 0.231, 3) satisfaction work profession involvement (X3) (Y), coefficient path (y3) = 0.324, 4) convert leadership organization (X1) against satisfaction work (X3), value coefficient path (Beta 31) = 0.285, 5) value coefficient path (32) = 0.492, 6) destination work (X3) value private (X2). because of that, to increase participation professionals need to strengthen leadership transformative and value personal as a variable exogenous, with satisfaction work as a variable intervention.